2013
DOI: 10.3762/bjoc.9.178
|View full text |Cite
|
Sign up to set email alerts
|

Molecular assembly of amino acid interlinked, topologically symmetric, π-complementary donor–acceptor–donor triads

Abstract: SummaryAmino acid interlinked pyrene and naphthalenediimide (NDI) based novel donor–acceptor–donor (D-A-D) triads are designed to exploit their topological symmetry and complementary π-character for facile charge-transfer complexation. Consequently, free-floating high-aspect-ratio supercoiled nanofibres and hierarchical helical bundles of triads are realized by modulating the chemical functionality of interlinking amino acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…ADA, triads (88) . They found that a relatively weak noncovalent CT interaction was achieved using symmetric and p-complementary pyrene and NDI . The Pantoş group studied, for the first time, the strength of aromatic donor–acceptor interactions between NDI and DAN derivatives within polymers using nonpolar solvents …”
Section: Supramolecular Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…ADA, triads (88) . They found that a relatively weak noncovalent CT interaction was achieved using symmetric and p-complementary pyrene and NDI . The Pantoş group studied, for the first time, the strength of aromatic donor–acceptor interactions between NDI and DAN derivatives within polymers using nonpolar solvents …”
Section: Supramolecular Self-assemblymentioning
confidence: 99%
“…They found that a relatively weak noncovalent CT interaction was achieved using symmetric and p-complementary pyrene and NDI. 212 The Pantoşgroup studied, for the first time, the strength of aromatic donor−acceptor interactions between NDI and DAN derivatives within polymers using nonpolar solvents. 213 Sanders et al 214 report the synthesis, self-assembly, and electron-transfer capabilities of peptide-based electron acceptor−donor−acceptor (A-D-A) systems.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…NDI is a highly π-acidic planar molecule with an estimated molecular quadrupole moment ( Q zz ) of +18.6 B (Buckinghams) that forms a unique pair with π-basic pyrene ( Q zz = −13.8 B) due to their topological structural similarity and the complementary π-character. ,, The alternate stacks of electron donor–acceptor based CT complexation is especially interesting due to high electrical conductivity and room-temperature ferroelectricity. However, the interaction energy for NDI–NDI (−27.17 kcal mol –1 ) stack is greater than those for NDI–pyrene (−23.35 kcal mol –1 ) and pyrene–pyrene (−16.45 kcal mol –1 ), and thereby self-sorting predominates over alternate stacking . We showed that NDI–pyrene dyads prefer alternate stacking (−53.62 kcal mol –1 ) over self-sorted assemblies (−43.62 kcal mol –1 ).…”
Section: Molecular Architectonicsmentioning
confidence: 99%
“…Concurrently, the chiral properties of the amino acid auxiliaries are manifested as a helical signature within these nanoarchitectures. 48,49 2.1.2. Amino Acid Chirality-Guided 2D Architectonics.…”
Section: D Architectures By Programmable Fabrication Strategiesmentioning
confidence: 99%
“…21,79,80 The molecular stability, predictable sequence specificity, molecular recognition characteristics, and the construction of regular and defined architectures through mutual templating of DNA and small functional molecules allow the custom design and engineering of a range of novel molecular and material architectures, which is also called templated DNA nanotechnology or DNA nanoarchitectonics. 79−82 We developed adenine (A) and thymine (T) functionalized NDIs, NDI-AA (48) and NDI-TT (49), and used them to template peptide nucleic acid (PNA) dimers, PNA-TT (50) and PNA-AA (51), respectively. 83 48 and 49 individually assemble into nanoribbon and nanobelt structures, respectively (Figure 6a,b), via hydrogen bonding and weak aromatic interactions.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%